2014
DOI: 10.3109/02713683.2014.903498
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fractal Contact Lenses on Peripheral Refraction in Myopic Model Eyes

Abstract: Visual acuity and contrast sensitivity with iPad 2 2. Structured abstract. PurposeTo present two iPad applications (apps) for measuring Visual Acuity (VA) and Contrast Sensitivity Function (CSF) and to assess reliability and agreement with a commercial screening device. MethodsForty-five healthy subjects with monocular corrected visual acuities better than 0.2 logMAR participated in the agreement study of VA and CSF with iPad and Optec 6500. Results MD of VA was 0.06 logMAR better with AmblyopiaVA than with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…In our design, this limitation could be easily solved since the treatment power this is a free parameter that affects the peripheral refractive error without compromising the central vision, at least for pupil diameters lower than 4.0 mm. 10 For the nacked eye, we found that corneal asphericity along temporal and nasal semichords in the horizontal meridian was negatively correlated with the M component; but only for temporal cornea and nasal retina whereas for J45 and J0 the negative correlations where found between nasal cornea and temporal retina ( Table 1). This is also in agreement with theoretical models, which assert that the more positive is Q, the more myopic is the peripheral refraction induced for M and J0.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In our design, this limitation could be easily solved since the treatment power this is a free parameter that affects the peripheral refractive error without compromising the central vision, at least for pupil diameters lower than 4.0 mm. 10 For the nacked eye, we found that corneal asphericity along temporal and nasal semichords in the horizontal meridian was negatively correlated with the M component; but only for temporal cornea and nasal retina whereas for J45 and J0 the negative correlations where found between nasal cornea and temporal retina ( Table 1). This is also in agreement with theoretical models, which assert that the more positive is Q, the more myopic is the peripheral refraction induced for M and J0.…”
Section: Discussionmentioning
confidence: 74%
“…In most of the clinical studies, the study of the effect of the proposed solutions was restricted to the analysis of the RPRE, measured in terms of vector components M, J0 and J45 along the horizontal meridian, 3,6 and only few include the vertical and oblique meridians. [19][20][21] In this work we have presented the first clinical study in which the ability of a new design of CLs [10] to create a RPRE in the whole 2D visual field has been demonstrated. Taking into account that, on the one hand, the mean power at the treatment zones (+1.32 D) of the manufactured lenses was lower than the theoretical labelled power (+2.00 D); and, on the other hand, that lens prototypes were decentered during the RPRE measurements an excellent agreement between the theoretical and experimental results has been obtained (see Fig.5A).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations